2003
DOI: 10.1002/ana.10720
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind controlled trial of bilateral fetal nigral transplantation in Parkinson's disease

Abstract: Thirty-four patients with advanced Parkinson's disease participated in a prospective 24-month double-blind, placebo-controlled trial of fetal nigral transplantation. Patients were randomized to receive bilateral transplantation with one or four donors per side or a placebo procedure. The primary end point was change between baseline and final visits in motor component of the Unified Parkinson's Disease Rating Scale in the practically defined off state. There was no significant overall treatment effect (p = 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
1,179
8
17

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,440 publications
(1,217 citation statements)
references
References 38 publications
13
1,179
8
17
Order By: Relevance
“…Thus, these data suggest that supplementing intrastriatal fetal VM grafts with in vivo injections of viral vector delivering the GDNF gene may decrease the number of VM grafts necessary to re-supply the host striatum with adequate levels of DA. This would be a significant achievement, as the use of eight donors for one human host (Hauser et al, 1999;Olanow et al, 2003) is an obstacle to neural grafting as a treatment option for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these data suggest that supplementing intrastriatal fetal VM grafts with in vivo injections of viral vector delivering the GDNF gene may decrease the number of VM grafts necessary to re-supply the host striatum with adequate levels of DA. This would be a significant achievement, as the use of eight donors for one human host (Hauser et al, 1999;Olanow et al, 2003) is an obstacle to neural grafting as a treatment option for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some parkinsonian patients that received fetal VM grafts in recent clinical trials developed off-medication dyskinesias or graft-induced dyskinesias (GID) (Freed et al, 2001;Hagell et al, 2002;Olanow et al, 2003). The proportion of patients in these 3 studies with GID severe enough to constitute clinical therapeutic problems has been estimated to be between 7 and 15% (Hagell and Cenci, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopaminergic Grafts Can Survive and Become Morphologically Integrated in the PD Patient's Brain Following implantation of postmitotic DA neuroblasts from the ventral mesencephalon of 6-to 9-weekold human fetuses, positron emission tomography (PET) detected increases in 6-L-[ 18 F]-fluorodopa ( 18 F-dopa) uptake ( Fig. 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and histopathological studies have shown long-term, extensive synaptic reinnervation in the striatum [13,[20][21][22][23][24][25][26][27].…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 99%
“…No hay que olvidar que esta situación se aplica a enfermedades muy prevalentes y con gran impacto social, como el accidente cerebrovascular, la lesión cerebral y medular postraumática, o las enfermedades neurodegenerativas, para las que no existe actualmente alternativa de tratamiento curativo. El aparente fracaso del uso de injertos de células diferenciadas con capacidad de liberar neurotransmisores, fundamentalmente de mesencéfalo fetal en la enfermedad de Parkinson (EP) 45 , ha renovado el interés de la investigación con células troncales neurales (CTN). Aunque no existe evidencia para asegurar que la terapia celular con CTN es superior al uso de neuronas primarias en injertos fetales, su uso puede permitir la disponibilidad de un número elevado de células en distintos grados de diferenciación, y su manipulación in vitro, ambiental o genética, para mejorar su supervivencia, diferenciación, migración e integración 46 .…”
Section: Regeneración Neurológicaunclassified